SIMPLE AND PRECISE UV SPECTROPHOTOMETRIC METHOD DEVELOPMENT FOR ESTIMATION OF ALBENDAZOLE FOR DISSOLUTION STUDY (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Albendazole is a class II drug in biopharmaceutical classification system, so its dissolution study is very difficult because of its low solubility and difficulty during estimation of drug in bulk. The present study deals with UV spectrophotometric method development and validation for estimation of albendazole in bulk form. Albendazole is a benzimidazole derivative with an oral broad spectrum of activity against human and animal helminthes parasites. The drug obeyed the Beer’s law and showed good correlation. It showed absorption maxima at 229nm in 0.1 N HCL with 0.05% sodium lauryl sulphate (SLS). The linearity was observed between 4-20μg/ml. The method was applied for the analysis of the drug in the pure, tablet and suspension forms. The slope and intercept of the equation of the regression line are 0.009 and 0.017 respectively. Correlation coefficient was found to be 0.9996. The results of analysis were validated by recovery studies. The recovery was more than 97%. The method was found to be simple, reliable, rapid, precise, specific and reproducible and can be applied for routine analysis of albendazole in different dosage form and dissolution studies.